(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This research aimed to determine the performance of the District Attorney’s Office in Handling Corruption Cases in Enrekang Regency. This study used qualitative research. Data collection techniques were observation and interviews. The number of informants in this study was 5 people. Data analysis used an interactive analysis model. The results of this study showed that the performance of the district attorney’s office in handling corruption cases was quite good but needs to be improved to be more optimal, this was seen from the aspect of the quality of each report received by the Attorney’s office originating from public reports and from other parties, the quantity for the number of investigators in completing each case required an average of 3 investigators, the timeliness of each employee was required to perform their duties quickly so that they usually finished the task or work in accordance with the time given, the effectiveness of the Attorney’s office was good enough, both in terms of work reports, and completion every task or job, because it had worked in accordance with the guidelines and direction.